Peran literasi informasi dalam menghadapi arus informasi digital dan penyebaran hoaks di era digital - Syukur, Najma Mumtaz (Maliki Interdisciplinary Journal, 2026)
The development of information and communication technology has brought society into the digital age, characterized by a rapid, abundant, and unstoppable flow of information through various social media platforms and websites. Although easy access to information provides many benefits, this condition also poses a serious challenge in the form of an increase in the spread of false information or hoaxes, which are often accepted and shared without verification. The public's low ability to evaluate the sources and credibility of information is a major factor that reinforces the spread of hoaxes in the digital space. This study aims to analyze the role of information literacy as a key competency in dealing with the rapid flow of digital information and minimizing the negative impact of the spread of hoaxes. Using a qualitative descriptive approach, data were obtained through interviews, observations, and documentation studies of active social media users and students. The results of the study show that information literacy plays an important role in shaping critical thinking skills, accuracy in assessing the validity of information, and responsibility in the use and dissemination of digital information. Individuals with good information literacy are proven to be more capable of identifying misinformation, cross-checking, and being selective before sharing information. This study confirms that strengthening information literacy through the role of educational institutions and libraries is a strategic step in creating a society that is more critical, intelligent, and wise in interacting with digital information.